A high-performance nanobridged MoO3 UV photodetector based on nanojunctions with switching characteristics. (15th December 2016) - Zheng, Qinghong; Huang, Jin; Yang, Haiyang; Chen, Yanqin
Abstract: Ultraviolet photodetectors (UVPDs) were fabricated via the in situ growth of orthorhombic MoO3 nanobelts among interdigital electrodes. Two types of nanojunction, touching and interpenetration, were formed between neighboring nanobelts at different growth conditions. The photoresponse mechanism of the UVPDs greatly depends on the type of nanojunction. Nanojunctions formed with touching nanobelts possess switching characteristics due to the barrier height variation along with the UV illumination. The UVPD with the touching structure exhibits low noise, high UV sensitivity and fast speed, having a dark current of 1.4 nA, an on/off ratio of over 100 and a response time of below 1 s, at an applied voltage of 10 V. The enhanced performance can be attributed to the switching characteristics of the touching nanojunction.